Biomechanical Analysis of Throwing Techniques in Kurash: Implications for Performance Optimization and Injury Prevention (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the biomechanical characteristics of major throwing techniques in Kurash to identify performance-enhancing factors and injury risk mechanisms. Three commonly used throws – galtaq (leg sweep throw), yelka ortidan otish (shoulder throw), and bel otar (hip throw) – were analyzed using 3D motion capture and force plate systems. Results showed that optimal technique execution required coordinated triple extension, precise center of mass manipulation, and balanced ground reaction forces. Identifying biomechanical inefficiencies can guide coaches in refining technique and implementing injury prevention strategies for Kurash athletes.